Biallelic variants in TTC21B as a rare cause of early‐onset arterial hypertension and tubuloglomerular kidney disease. Issue 1 (15th March 2022) - Olinger, Eric; Phakdeekitcharoen, Pran; Caliskan, Yasar; Orr, Sarah; Mabillard, Holly; Pickles, Charles; Tse, Yincent; Wood, Katrina; ,; Sayer, John A.
Abstract: Monogenic disorders of the kidney typically affect either the glomerular or tubulointerstitial compartment producing a distinct set of clinical phenotypes. Primary focal segmental glomerulosclerosis (FSGS), for instance, is characterized by glomerular scarring with proteinuria and hypertension while nephronophthisis (NPHP) is associated with interstitial fibrosis and tubular atrophy, salt wasting, and low‐ to normal blood pressure. For both diseases, an expanding number of non‐overlapping genes with roles in glomerular filtration or primary cilium homeostasis, respectively, have been identified. TTC21B, encoding IFT139, however has been associated with disorders of both the glomerular and tubulointerstitial compartment, and linked with defective podocyte cytoskeleton and ciliary transport, respectively. Starting from a case report of extreme early‐onset hypertension, proteinuria, and progressive kidney disease, as well as data from the Genomics England 100, 000 Genomes Project, we illustrate here the difficulties in assigning this mixed phenotype to the correct genetic diagnosis. Careful literature review supports the notion that biallelic, often hypomorph, missense variants in TTC21B are commonly associated with early‐onset hypertension and histological features of both FSGS and NPHP. Increased clinical recognition of this mixed glomerular and tubulointerstitial disease with often mild or absent features of a typical ciliopathy as well as inclusion of TTC21B on gene panels for early‐onset arterial hypertension might shorten the diagnostic odyssey for patients affected by this rare tubuloglomerular kidney disease.